De teloorgang van de Nederlandse godsdienstwijsbegeerte: In gesprek met Willem B. Drees - Sarot, Marcel 1961- (2024)
The Decline of Dutch Philosophy of Religion: In Discussion with Willem B. Drees In response to Drees’ recount of the history of the Leyden chair in philosophy of religion, I inquire about the decline of philosophy of religion in Dutch universities since the 1980s. I argue that this decline is linked to the educational structure established in 1876, which separated theology into a state-controlled secular faculty and a church-controlled ministerial program. While officially secular, the state faculty was predominantly Protestant, with liberal Protestant scholars dominating. Philosophy of religion, taught mainly by liberal Protestant theologians, played a pivotal role in providing the theological synthesis that had traditionally been provided by dogmatics. However, with the emergence of religious studies in the 1980s, philosophy of religion, perceived as too entrenched in theological discourse, struggled to find acceptance.
Keywords: Leyden University; Liberal Theology; Philosophy of religion